A variant of the pinwheel tiling - Ferrari, Mariano Andrés (2006)
In this paper, a number of new generating relations are obtained for general triple hypergeometric series by using integral operators. Results involving double series and hypergeometric functions of Srivastava, Appell and Humbert are obtained as applications of these generating relations.